Realising governmentality: Pastoral power, governmental discourse and the (re)constitution of subjectivities. Issue 6 (November 2018) - Martin, Graham P.; Waring, Justin
Michel Foucault's concept of governmentality has been hugely influential in sociology and other disciplinary fields. However, its application has been criticised by those who suggest it neglects agency, and gives overwhelming power to governmental discourses in constituting subjectivities, determining behaviour and reproducing social reality. Drawing on posthumously translated lecture transcripts, in this article the authors suggest that Foucault's nascent concept of pastoral power offers a route to a better conceptualisation of the relationship between discourse, subjectivity and agency, and a means of understanding the (contested, non-determinate, social) process through which governmental discourses are shaped, disseminated and translated into action. The authors offer empirical examples from their work in healthcare of how this process takes place, present a model of the key mechanisms through which contemporary pastoral power operates, and suggest future research avenues for refining, developing or contesting this model.